Pemetaan Kebersihan dan Perilaku Aman Pangan (PEKA-PANGAN) Sebagai Upaya Peningkatan Derajat Kesehatan Masyarakat Tanjung Beringin - Amelia, Sri; Lubis, Nenni Dwi Aprianti; Lubis, Fahrurrozi; Delyuzar, Delyuzar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Food safety is a global issue that directly affects a person's health. Foods that are unsafe to consume will cause various diseases from diarrhea to cancer. Around 420,000 people die every year from food poisoning. Various measures to prevent food poisoning must be taken from an early age, such as washing hands before and during food processing, preventing cross contamination, cooking food thoroughly and so on. Various measures to prevent food poisoning must be taken from an early age, such as washing hands before and during food processing, preventing cross contamination, cooking food thoroughly and so on. This community service was carried out in Pekan Tanjung Beringin Village with the aim of knowing food safety in the area. Service activities are carried out through five stages, namely socialization, data collection, data analysis and mapping, counseling and focus group discussions, and cross-sectoral outreach. From the results of data collection and analysis, policies are created that aim to improve the level of public health, especially in terms of food safety. A total of 15 hamlets with 398 participants were included in this service activity. In general, hamlets 1-15 are considered good in terms of food processing. There are certain points that must be improved together by the community, the Community Health Center, and the local government in assisting proper and safe food processing in the Tanjung Beringin area.